Dynamics of Sea-level Changes in the Red Sea - Cheriyeri Poyil Abdulla (Current Advances in Geography, Environment and Earth Sciences Vol. 5, 2022)
Under the recent global climatic changes, the information on sea-level changes is very important for the proper understanding of upper-ocean processes. The information on sea-level changes in the Red Sea is significantly lacking, especially the information on interannual variability, long-term trends, and associated dynamics. The present study attempted to fill this gap by analyzing the satellite altimetry sea-level data for nearly three decades (1993–2020) and is used to understand the variability and associated dynamics in the Red Sea sea-level. The sea level is generally higher during winter with maximum in December–January and lower during summer with minimum in August, following a steady pattern from south to north. The variability in global climate modes, such as El-Nino Southern Oscillation events, East Atlantic-West Russian oscillation, and the Indian Ocean Dipole, is closely correlated with interannual variations in sea level. The El-Nino Southern Oscillation has a greater impact on sea level than other climatic patterns. From 1993 until the present, the Red Sea’s sea level rose at a rate of 3.88 mm/year, which was consistent with the global rate of 3.3 ± 0.5 mm/year. From 2000 until the present, the Red Sea experienced a considerably quicker rate of sea-level rise (6.40 mm/year).